2018
DOI: 10.1136/bmjopen-2018-022126
|View full text |Cite
|
Sign up to set email alerts
|

What are the perceived influences on asthma self-management at the workplace? A qualitative study

Abstract: ObjectivesAsthma can represent a substantial challenge to the affected individual, but is usually well controlled by adequate asthma self-management behaviour (SMB). Asthma SMB comprises symptom prevention, symptom monitoring, acute symptom management and communication with important others. The implementation of asthma SMB seems to depend on contextual factors. For employed adults, working conditions may be important in this respect. We, therefore, aimed to explore the perceived influences on effective asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Prior to the study, a topic guide was developed by Adrian Loerbroks (AL) and Thomas Muth (TM) and two medical students (SS and CB) to facilitate focus group discussions (the topic guide can be found in Additional file 1). AL and TM have a vast knowledge of the current stress literature, are experienced in qualitative research [26, 27], and are teaching staff of the medical school. Furthermore, TM has close contact with medical students in his role as coordinator and contact person for elective courses at our institute.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the study, a topic guide was developed by Adrian Loerbroks (AL) and Thomas Muth (TM) and two medical students (SS and CB) to facilitate focus group discussions (the topic guide can be found in Additional file 1). AL and TM have a vast knowledge of the current stress literature, are experienced in qualitative research [26, 27], and are teaching staff of the medical school. Furthermore, TM has close contact with medical students in his role as coordinator and contact person for elective courses at our institute.…”
Section: Methodsmentioning
confidence: 99%
“…During analysis these categories were further broken down into sub-categories by inductive category formation. After MD completed the first coding round of 25% of the data, AL, an experienced qualitative researcher [29,30,32,33], reviewed the coding scheme. The coding scheme was then adapted and a second coding round was performed by MD.…”
Section: Discussionmentioning
confidence: 99%
“…Effective asthma self‐management behaviour (SMB)—e.g., symptom prevention or acute symptom management [1 ]—can improve the control of asthma and its prognosis [2 ]. The actual implementation of SMB is partially determined by contextual factors [1 ], e.g., by the working conditions employees with asthma are exposed to [3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative interview study among employees with asthma suggested that two specific elements of well‐established work stress models play a crucial role in the effective implementation of asthma SMB at work [3 ]: job decision latitude (JDL; i.e., the control over one's tasks and when and how to complete them [4, 5 ]) and social support by colleagues and line‐managers [6–8 ]. The two factors subjectively related to different domains of asthma SMB: high JDL seemed to promote symptom prevention, symptom monitoring, and acute symptom management, whereas support was perceived to facilitate symptom prevention, acute symptom management and communication (e.g., self‐disclosure of one's condition) [3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation